Honey production from selected Apis mellifera colonies and its relation to geographic-environmental parameters of Jalisco: Honey production and environmental-geographical parameters - Tapia-González, José María; Martínez- Serratos, Tomás; Macias-Macias, José Octavio; Contreras-Escareño, Francisca; Rivera-Espinoza, Ma. Patricia; Rodríguez-López , Enrique; Tapia-Rivera, Jose Carlos (Ecosistemas y Recursos Agropecuarios, 2021)
The objective of the study was to relate the honey production of the selected Apis mellifera colonies with geographic-environmental parametersof southern Jalisco. The honey production of 9,169 colonies was measured, 352 were selected, those that produced more than 25 kg. The honey production of these colonies was 40.8 6.7 kg. In the mountain region, temperature was moderately negatively correlated with honey production (r = -0.448, P < 0.001) and moderately positive with rainfall (r = 0.448, P < 0.001). In the valleys region, altitude presented low negative correlation with honey production (r = -0.121) (P < 0.03), low positive correlation with temperature (r = 0.359, P < 0.001) and moderate correlation with rainfall (r = 0.630, P < 0.001). It is concluded that honey production, rainfall and environmental temperature are statistically related in southern Jalisco.